2006
DOI: 10.1152/jn.00205.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Persistent Na+ Current and M-Type K+ Current to Somatic Bursting in CA1 Pyramidal Cells: Combined Experimental and Modeling Study

Abstract: The intrinsic firing modes of adult CA1 pyramidal cells vary along a continuum of "burstiness" from regular firing to rhythmic bursting, depending on the ionic composition of the extracellular milieu. Burstiness is low in neurons exposed to a normal extracellular Ca(2+) concentration ([Ca(2+)](o)), but is markedly enhanced by lowering [Ca(2+)](o), although not by blocking Ca(2+) and Ca(2+)-activated K(+) currents. We show, using intracellular recordings, that burstiness in low [Ca(2+)](o) persists even after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
190
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(234 citation statements)
references
References 78 publications
(82 reference statements)
16
190
1
Order By: Relevance
“…Therefore, I NaPdriven bursting can result from an increase in I NaP or, conversely, from a decrease in I M (Golomb et al, 2006). Our results strongly suggest that hyposmotic ADP facilitation and bursting is mediated by I M inhibition rather than by I NaP enhancement.…”
Section: Inhibition Of I M Underlies Hyposmotic Spike Adp Facilitatiomentioning
confidence: 57%
See 1 more Smart Citation
“…Therefore, I NaPdriven bursting can result from an increase in I NaP or, conversely, from a decrease in I M (Golomb et al, 2006). Our results strongly suggest that hyposmotic ADP facilitation and bursting is mediated by I M inhibition rather than by I NaP enhancement.…”
Section: Inhibition Of I M Underlies Hyposmotic Spike Adp Facilitatiomentioning
confidence: 57%
“…We found that hyposmotic bursting is readily suppressed by blocking I NaP , whereas blockage of Ca 2ϩ channels causes burst prolongation. The obvious conclusion is that hyposmotic bursting is driven predominantly by I NaP , whereas recruitment of Ca 2ϩ currents mediates burst termination likely by activating Ca 2ϩ -gated K ϩ currents (Golomb et al, 2006).…”
Section: Ionic Mechanism Of Hyposmotic Burstingmentioning
confidence: 99%
“…When the trajectory (gray curve in Fig. 1) slides along the stable equi- Several conductance-based models can give rise to square-wave bursting, including those built to study systems as diverse as pancreatic β-cells [19,26], neurons in the pre-Bötzinger complex of the brain stem [27,28] or hippocampal ca1 pyramidal cells [29]. Our analysis can be applied to any of these or even other systems, provided that bursting involves a saddle middle branch in the equilibrium curve of the fast subsystem.…”
Section: B Neuron Modelmentioning
confidence: 99%
“…The existing findings have proved that AD can cause electrophysiological characteristics' change of the hippocampal neuron, and especially can cause change of the potassium ion channel characteristics [1,18,21]. Dependent on electrophysiological experiments and new technologies, such as optics imaging, some models of hippocampal pyramidal neurons based on ionic conductance have been successfully constructed [3,4,5,6,9,[11][12][13][14]19,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The bursting mechanism is different from the 'ping-pong' mechanism, which depends on integrity of apical dendrites [25][26][27]. Based on the CA1 pyramidal neuron's membrane ionic channel theory and its electrophysiological experimental data, according to the basic frames of the Hodgkin-Huxley(H-H) class of neuron models, Golomb et al developed the one-compartment model of CA1 pyramidal neuron [5], which is different from the former multi-compartment cable model of the hippocampal pyramid neuron. This model omits effects of apical dendrites and its complexity is reduced, which not only can simulate many electrophysiological features and experimental results of the hippocampal CA1 pyramid neuron, but also can spontaneously generate regular firing, tonic firing, and rhythmic bursting.…”
Section: Introductionmentioning
confidence: 99%